Pemberian kompres air hangat dan aromaterapi mawar terhadap penurunan nyeri pada ibu bersalin kala I fase aktif - Fazdria Fazdria; Henniwati Henniwati; Alchalidi Alchalidi; Eva Sulistiany; Elfida Elfida (Poltekkes Kemenkes Aceh, 2024)
Background: Pain during labor is a discomfort that often occurs in mothers. Severe pain can make the mother stressed, uncomfortable and exhausted. Uterine contractions during the initial phase of labor cause labor pain. The number of supplementary treatment that can be given to laboring mothers in lowering the pain felt, among them is aromatherapy and warm compresses.Objectives: To find out the difference between warm water compresses and rose aromatherapy to reduce pain in maternity mothers during the active phase I.Methods: This type of research is quasi experimental with a research design of nonequivalent control group design. The number of samples was 60 laboring mothers in the working area of the West Langsa Health Center, which was divided into 2 groups of 30 people in the warm compress group and 30 people in the rose aromatherapy group. The research was conducted on September 12 to November 28, 2023. The instrument used was an observation sheet containing respondent data and the NRS pain scale. Warm compresses are given for 20 minutes using buli-buli on the lower back and rose aromatherapy as much as 4 drops in a humiedifer containing water which is given for 20 minutes, the intervention is given at the time of the active phase. Data processing using Wilcoxon test to see the effect of each variable and man whitney test to determine which intervention is more effective.Results: Giving warm compresses and rose aromatherapy is effective in reducing labor pain in laboring women in the first phase of the active phase with a significance value of 0,000 and warm compresses and aromatherapy are equally effective in reducing labor pain with a significance value of 0,000.Conclusion: Giving warm compresses and rose aromatherapy is equally effective in reducing labor pain in the first phase of active labor.